Potensi Penetralisir Radikal Bebas Rimpang Temu Lawak (Curcuma xanthoriza Roxb.) dan Temu Ireng (Curcuma Aerugonosa Roxb.) - Setyaningrum Ariviani (Universitas Sebelas Maret, 2005)
Solvent with different polarity used used in extraction of antioxidant compound from temu Lawak (Curcuma xanthoriza Roxb.) and Temu Ireng (Curcuma Aerugonosa Roxb.) spices. The solvent are Enthanol and acetone. Antioxidant extracts were analyzed in “neutralizer free radical” activity with DPPH Radical Scavenging Method. The activity compared with synthetic antioxidant BHA.Result of the research perform that Temu Lawak and Temu Ireng spices were potential as neutralizer free radical. Antioxidant extract of Temu Lawak spices have higher activity than Temu Ireng spices extract. The “neutralizer free radical” activity of 1% Temu Lawak extract is 1,9 times 300 ppm BHA activity, and 1% Temu Ireng extract is 1,24 times 300 ppm BHA activity. Solvent influential at “neutralizer free radical” activity of Temu Ireng spices extract, but it doesn’t influential at Temu lawak spices extract.